Pengaruh Profitabilitas, Islamic Corporate Governance, dan Maqashid Sharia Index Terhadap Nilai Perusahaan dengan Islamic Social Reporting pada Bank Syariah Indonesia - Tarisa Amanda Melyana Sari; Zainal Alim Adiwijaya (eCo-Buss, 2025)
Sharia banks have an important role in supporting the national economy, but the level of sharia financial literacy and inclusion in Indonesia still lags far behind conventional banking. This condition requires improvements in governance quality, profitability, and sharia compliance to strengthen corporate value. This research aims to analyze the influence of profitability, Islamic Corporate Governance (ICG), and the Maqashid Syariah Index (MSI) on corporate value, with Islamic Social Reporting (ISR) as a moderating variable. The research method uses a quantitative explanatory research approach with secondary data in the form of financial statements and GCG reports from eight Islamic Commercial Banks in Indonesia for the period 2018–2023, processed using SmartPLS 4. The results indicate that profitability, ICG, and MSI do not significantly influence firm value, while ISR is found to moderate the influence of ICG and MSI on firm value but does not moderate the relationship between profitability and firm value. These findings emphasize the importance of ISR in strengthening the role of Islamic governance and the achievement of Islamic objectives in increasing company value. Therefore, Islamic banks are advised to expand ISR disclosure as a strategy to build investor confidence, while enhancing competitiveness through strengthening Islamic aspects, product innovation, and governance transparency.